Tradycyjna edukacja dzieci żydowskich (wprowadzenie do problemu) - Grzesiak, Hanna (Biuletyn Historii Wychowania, 2010)
The birth of a child in a Jewish family, both in the ancient times and today, brings happiness not only to the parents themselves but also to the whole of the Jewish community. Children are a gift from God, they contribute to the prosperous future of the family they come from, but they also, what is essential, guarantee the continued survival of the chosen nation. Following this assumption, childless families were considered to be deficient, unsubstantial and were shunned from society because, as the Israelites believe, God blesses only those who have numerous offspring. The lack of children was often considered a curse, equated to punishment for sins and the absence of God in the family. The present article introduces the reader to the principles of traditional education of Jewish children, outlines problems of child’s education both at home, which is a fundamental basis for creating and shaping Jewish identity, and at school, where the emphasis is on transferring knowledge of religious and moral nature. Additionally, educational methods used both at family home and educational establishments are also discussed in the article.